Problems of Upstream and Downstream Integration of Rare Earth Metals in the National Mining Legal System - Ade Zamrah; Boy Nurdin (Journal Customary Law, 2026)
Rare Earth Metals play a strategic role in the development of high-tech industries and the global energy transition. Indonesia, a country with abundant mineral resources, faces the challenge of integrating upstream mining activities with downstream policies aimed at increasing added value. This study analyzes the problematic integration of upstream and downstream Rare Earth Metals within the national mining legal system, specifically based on Law Number 3 of 2020 and its implementing regulations, including Minister of Energy and Mineral Resources Regulation Number 18 of 2025. The method employs normative legal research with legislative, conceptual, and systemic approaches. The study results reveal a disharmony between extraction-based licensing designs and downstreaming obligations, which have not been integrated from the initial stages of permit issuance. Regulatory fragmentation and overlapping authority between sectors also impact the effectiveness of value-added policies. The absence of an institutional model specifically addressing critical minerals has hindered the development of the national value chain. The study proposes a reconstruction of value chain-based licensing designs, cross-sectoral regulatory harmonization, and the establishment of an integrative institutional model as steps toward industrial sovereignty. This approach is expected to strengthen the sovereignty of Rare Earth Metal management while simultaneously encouraging a sustainable transformation of the strategic resource-based economy.